The effect of activated charcoal and peptone on seeds germination of brassavola nodosa, cattleya intermedia, dendrobium lasianthera and gastrochilus patinatus / Nurulathirah Mohd Yusoff - Mohd Yusoff, Nurulathirah (2013)
Activated charcoal (AC) and peptone have been used in micropropagation of plants in tissue culture to improve the seeds development of the plant. The aim of this study is to examine the influence of AC and peptone on the seeds germination of orchids; named, Brassavola nodosa, Cattleya intermedia, Gastrochilus patinatus and Dendrobium lasianthera. The seeds were sown on half strength Murashige and Skoog (1/2 MS) medium supplemented with different concentrations of AC (0.0, 0.5, 1.0, 2.0 g/L) and peptone (0.0, 0.5, 1.0, 2.0 g/L) by using Complete Randomized Design (CRD) method. Three replicates of each media were utilized. The percentage of protocorm and number of shoots induced were observed after 16 weeks. The results showed that Brassavo/a nodosa exhibited the highest percentage of protocorm and number of shoots than the other three species. The most optimum growth for Brassavola nodosa was in the media that was supplemented with 2.0 g/L peptone and without AC while the least growth was observed in media that is supplemented with 2.0 g/L AC and without peptone. For Dendrobium lasianthera, the highest percentage of protocorm and shoots was found in 1.0 g/L peptone and 0.0 g/L AC while the media supplemented with 2.0 g/L AC and 0.0 g/L peptone showed the least growth. For Cattleya intermedia, moderate growth of protocorm was observed in media supplemented with 0.5 g/L peptone and 1.0 g/L AC while the other media showed no development. Gastrochilus patinatus did not showed any growth development in media investigated. The result showed that the addition of AC and peptone could enhance the seeds development of most orchid species that was investigated in this study except for Gastrochilus patinatus.